Remodeling and activation mechanisms of outer arm dyneins revealed by cryo‐EM. (2nd August 2021) - Kubo, Shintaroh; Yang, Shun Kai; Black, Corbin S; Dai, Daniel; Valente-Paterno, Melissa; Gaertig, Jacek; Ichikawa, Muneyoshi; Bui, Khanh Huy
Abstract: Cilia are thin microtubule‐based protrusions of eukaryotic cells. The swimming of ciliated protists and sperm cells is propelled by the beating of cilia. Cilia propagate the flow of mucus in the trachea and protect the human body from viral infections. The main force generators of ciliary beating are the outer dynein arms (ODAs) which attach to the doublet microtubules. The bending of cilia is driven by the ODAs' conformational changes caused by ATP hydrolysis. Here, we report the native ODA complex structure attaching to the doublet microtubule by cryo‐electron microscopy. The structure reveals how the ODA complex is attached to the doublet microtubule via the docking complex in its native state. Combined with coarse‐grained molecular dynamic simulations, we present a model of how the attachment of the ODA to the doublet microtubule induces remodeling and activation of the ODA complex. Synopsis: Cryo‐EM structure of the outer dynein arm (ODA) complex attached to the doublet microtubule combined with the coarse‐grained molecular dynamics (MD) simulation reveals the active conformation of the ODA and the activation mechanisms of the ODA complex. ODA complex structure natively bound to the doublet microtubule via its tail domain was obtained by cryo‐EM. The dynein heavy chain heads of the ODA complex interact with the tail domain of the next ODA complex, forming a row of ODA complexes on the doublet microtubule. Comparison of active and inactive conformation the ODA complex revealed the remodeling of the ODA complex structure, in particular the dynein heavy chain tails. Coarse‐grained MD simulation suggests that the attachment of the ODA complex to the doublet microtubule triggers the activation of the complex. Abstract : Cryo‐EM structure of the outer dynein arm (ODA) complex attached to the doublet microtubule combined with the coarse‐grained molecular dynamics (MD) simulation reveals the active conformation of the ODA and the activation mechanisms of the ODA complex.